Technoeconomic Analysis of Ducted Wind Turbines and Their Slow Acceptance on the Market - Masukume, Peace-Maker; Makaka, Golden; Tinarwo, David (Journal of Renewable Energy, 2014)
The encasing of wind turbines in a duct to enhance performance is not new. A ducted wind turbine produces more power than an unducted wind turbine of the same parameters. A number of approaches in studying the effects of diffusers and other wind concentrating devices have been done and have resulted in a number of prototypes produced but without any commercialization. The aim of this paper is to investigate the failure of commercialization of ducted turbines. A technical and economic analysis of a ducted turbine is also presented. The work shows that traditional economic methods used to evaluate ducted wind turbines are erroneous; they do not account for external effects of power generation and individual and community benefits derived from this technology. Failure to penetrate the market is due to negative publicity as a result of the erroneous evaluation undertaken and lack of appropriate engineering techniques to protect ducted wind energy systems in extreme wind conditions.